EFFECT OF SPRAYING WITH VITAMIN B9 AND E, AND THE AMINO ACID ARGININE OF SOME GROWTH CHARACTERS FOR TWO VARIETIES OF MAIZE - Rusol. I. A.; N. H. Zeboon (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate effect of some growth traits for two varieties of maize (Zea mays L.) to spraying vitamin B9 (folic acid), vitamin E (tocopherol), and arginine acid. A field experiment was conducted at the Agricultural Research Station, College of Agricultural Engineering Sciences - University of Baghdad, during the fall seasons of 2021 and 2022. Randomized complete block design (RCBD) within split plot arrangement with three replicates was used. The experiment included two factors, the first factor within the main plots represented two varieties of maize (Baghdad 3 and Sarah), while the second factor in the sub-plot represented spraying with vitamin E and B9 at concentrations of 1and 2 g L-1 and arginine acid at concentrations of 100 and 200 mg L-1, in addition to the control treatment (without spraying). The results showed that Sarah variety out performed in most studied traits for both seasons (75% silking , number of days from sowing to physiological maturity, dry weight, plant growth rate . physiological maturity, and leaves chlorophyll content.The growth characteristics were affected by spraying vitamin E, as the concentration exceeded 2 g L-1 in most traits, as the highest means were gave for 75% of silking (61.33 and 63.67 day), dry weight (387 and 425.3 g plant-1),and plant growth rate at physiological maturity (3.66 and 3.95 g plant-1 day-1) Leaf chlorophyll content (42.98 and 42.84 mg g-1 fresh weight) for both seasons.